Cameron Battle and the hidden kingdoms - Perry, Jamar J (Bloomsbury, 2022)
When Cameron and his best friends are magically transported through the pages of an ancestral book to the fabled West African country Chidani, they find a kingdom in extreme danger and have to find a way to save the Igbo people.